2004
DOI: 10.1038/sj.bjc.6601616
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of neoadjuvant paclitaxel and cisplatin for operable and locally advanced breast cancer: analysis of 126 patients

Abstract: In an earlier study, we have demonstrated a high clinical and pathologic response rate of neoadjuvant paclitaxel (P) and cisplatin (C) for patients with locally advanced breast cancer (LABC). The current phase II study includes larger number of patients who had longer follow-up. A total of 126 consecutive patients with noninflammatory LABC (T2 44 cm, T3 or T4, N0 -N3, M0) were included in the study. Patients were scheduled to receive three to four cycles of the neoadjuvant PC (paclitaxel 135 mg m À2 and cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Several cisplatin-based regimens have been tested in the neo-adjuvant setting, showing high anti tumour activity (Orlando et al, 2001;Ezzat et al, 2004). In the mid-nineties, we started the assessment of a weekly triplet regimen including cisplatin, epirubicin, and paclitaxel (PET regimen) in breast cancer patients (Frasci et al, 1999).…”
mentioning
confidence: 99%
“…Several cisplatin-based regimens have been tested in the neo-adjuvant setting, showing high anti tumour activity (Orlando et al, 2001;Ezzat et al, 2004). In the mid-nineties, we started the assessment of a weekly triplet regimen including cisplatin, epirubicin, and paclitaxel (PET regimen) in breast cancer patients (Frasci et al, 1999).…”
mentioning
confidence: 99%
“…Clinical and pathological responses may remain the most important variables in predicting breast cancer outcome after chemotherapy. Furthermore, patients experiencing a pathologic complete response (pCR) have a statistically signiWcant survival beneWt [1,2]. Liedtke [1] reported that triple-negative breast cancer with a pCR has excellent survival.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical data indicate that the combination of docetaxel, cisplatin and trastuzumab (TCH) may have the potential for clinically signiWcant activity against breast cancers that overexpress the her2/neu gene (HER2) [1][2][3]. The potential advantage of neoadjuvant chemotherapy is in the ability to assess the response rate in vivo and in downstaging the primary tumor and regional lymphatic metastases, which improves the cosmetic result.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We started studying platinumbased regimens in 1995, and have demonstrated the significant efficacy of the combination of paclitaxel and cisplatin in the management of patients with metastatic breast cancer [20]. In an earlier phase II paclitaxel and cisplatin utilized in patients with LABC, the regime was very effective with reasonable toxicities and high pathologic complete response rate [21,22].…”
Section: Introductionmentioning
confidence: 99%